Analisis Bibliometrik Perkembangan Penelitian Islam Moderat - Adnan Sulaiman (Gunung Djati Conference Series, 2023)
By being published in numerous scientific domains, a number of studies about moderate Islam continue to advance. By gathering and examining papers from 2013 through 2022, this project seeks to identify research trends relating to moderate Islam. In order to learn more about the dynamics of the emergence of moderate Islam, this research uses bibliometric analysis on a database acquired from Dimensions. Choosing keywords, finding the data, choosing articles, validating the data, and analyzing the data were the five steps we used in conducting this study. The author and associated promotion of moderate Islam are analyzed through the development of historical and institutional publications using dimensions in this study. According to the findings of this study, Moderate Islamic Studies has piqued the interest of the community. Among the nations that helped moderate Islam spread and advance were Germany and Indonesia. The magazine Springer Reference Medizin has the most frequent publications. In addition, the ISLAMICA Journal of Islamic Studies has made strides, as have the most successful scholars of moderate Islam, like "Winfried Stöcker and Axel Max Gressner. His research in the areas of Islamic philosophy and social studies has shown to be the most fruitful in studying moderate Islam, therefore it may be utilized to shed light on how moderate Islam has evolved.